Analisis Loyalitas Pelanggan Ditinjau dari Nilai Pelanggan, Lokasi dan Persepsi Harga dengan Kepuasan Pelanggan sebagai Variabel Intervening pada Pelanggan Indomaret di Yogyakarta - Eva Suwarni; Ambar Lukitaningsih; Muinah Fadhilah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The retail business is a business that is directly related to consumers, so to be able to compete, retailers must be able to increase customer satisfaction which will have an impact on customer loyalty. The purpose of this study was to analyze the effect of customer value, location, price on customer satisfaction and customer loyalty at Indomaret Yogyakarta. The research method used is survey research by distributing questionnaires to 100 respondents who are Indomaret customers in Yogyakarta. Data analysis was performed by statistical descriptive and SEM-PLS analysis. The results of the study conclude: 1) There is a significant effect of customer value on customer satisfaction; 2) There is no significant effect of location on customer satisfaction; 3) There is a significant effect of price on customer satisfaction; 4) There is no significant effect of customer value on customer loyalty; 5) There is no significant effect of location on customer loyalty; 6) There is a significant effect of price on customer loyalty; 7) There is a significant effect of customer satisfaction on customer loyalty. Furthermore, customer satisfaction is able to mediate the effect of customer value and price on customer loyalty, but cannot mediate the effect of location on customer loyalty. Keywords: Customer Value, Location, Price, Customer Satisfaction, Customer Loyalty.